Prevalence of Gastroesophageal Reflux Disease (GERD) in Dyspepsia Patients in Primary Referral Hospital - Nikko Darnindro; Annela Manurung; Edi Mulyana; Arnold Harahap (The Indonesian Society for Digestive Endoscopy, 2018)
Background: Gastroesophageal reflux disease (GERD) is caused by reflux of stomach contents into the esophagus and give the typical symptoms as heartburn. The prevalence of GERD was vary around the world. Prevalence of GERD by endoscopy in Jakarta was 22.8%. Limited data exist to determine the prevalence and related factors of gastroesophageal reflux disease (GERD) in the population without alarm symptoms. Validated GERDq questionnaire can be used easily to diagnose GERD in primary health care. This study aims to know the prevalence of GERD and related factors.Method: This cross-sectional study was conducted in adult dyspepsia patients at General Hospital District of Cilincing from January to March 2016. A validated GERDq questionnaire and a single proportion sample size calculation were used. Results: The prevalence of GERD was 49%, in elderly participants the prevalence was 44%. Of the 104 consecutive participants, 33.7% were male and 66.3% were female. The mean age was 47.6 ± 15.4 years old. The rate of GERD was higher in females than in males (53 vs. 40%, p = 0.189), increased as the age of the participants increased (p = 0.059) and also increased as the body mass index (BMI) of the participants increased (p 0.05). GERD was present in 50% of active or former smokers (p 0.05), 33.3% of daily coffee drinkers (p 0.05), 56.2% of active or former alcohol consumers (p 0.05), and 57.4% of daily tea drinkers (p = 0.049).Conclusion: The prevalence of GERD in dyspeptic patient was still high. There is a relation between GERD and tea consumption.